Pengembangan Media Pembelajaran Handout Digital Berbasis Android - Pratama, Devangga Putra Adhitya; Sakti, Norida Canda (Jurnal Pendidikan Ekonomi Undiksha, 2020)
This research is based on the existence of gaps in the Powerpoint learning media when used in complex material discussions. The development of instructional media has the aim to determine the feasibility , find out responses and learning outcomes of student on digital handout learning media based on androidThis research was conducted to 20 students of class XI in the 1st Senior High School Puri Mojokerto by collecting data using interviews, documentation, and questionnaires that were analyzed through qualitative and quantitative data analysis. The research model utilized 4D consisting of define, design, develop, and disseminate stages. The outputs of research were Android-based digital handout learning media applications with the APK format. The validation results of Digital Handout media obtained proper conclusions with the details, i.e., material experts by 92.8%, media experts by 87.8%, evaluation experts by 84%, and question experts by 88%. Students resulted in the positive responses by 91.8% and induced an increase in learning outcomes, which relatively high, considering from an average Gain Score of 0.71 with the completeness of classical posttest amounting to 90%. Therefore, it can be concluded that based on the results, digital handout learning media can facilitate students' understanding through appropriate media with positif responsses and increase in learning outcomes.